HIFZH AL-â€˜IRá¸Œ DALAM TRANSFORMASI SOSIAL MODERN (Upaya Menjadikan Hifzhu Al-â€˜Irá¸ Sebagai MaqÄshid Al-DharÅ«rÄ«y) - Husamuddin MZ, Lc., M.A. (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2019)
The old maqÄshid theory which still survives and is popular among ushuliyÅ«n, there are five known as al-dharÅ«riyyÄt al-khamsah. The discourse to add al-dharÅ«riyyÄt al-khamsah to aldharÅ«riyyÄt al-sittah or al-sab'ah and so on, has been rolled out by ushuliyÅ«n figures, although the addition received mixed responses. One of the additional discourses is to make hifzhu al â€˜irdh part of al-dharÅ«riyyÄt. Such discourse has been offered by TÄj al-din al-subki in the book jamÃ¢u al-jawÄmiâ€™, as well as At-ThÅ«fi and Al-qarÄfi, only Al-qarÄfi is not so strict. The modern figure who offered the idea back was Yusuf Al-Qaradhawi who later received a positive response from Muhammad Ahmad Al-QayatÄ« in his dissertation. Al-SyÄthibi makes hifzhu al-â€˜irdh included in the category of hifzhu al-nafs. Likewise AlGhazali and Ibn Al-Hajib did not make hifzhu al-â€˜irdh included in the category of al-dharÅ«rÄ«y. This attitude is supported by modern maqÄshid figures including Ibn â€˜Ä€syur, Ramadan Al-Buthi and Ahmad Al-Raisuni. In addition there is also a third opinion offered by Ibn Zaghibah â€˜izz Al-Din who made hifzhul al-'irdh part of dharuriyat but not in the kulliyah category but included in the juzâ€™iyyah category. The study was conducted using descriptive analysis methods, with data library research techniques (library research), the approach taken was a sociological approach. The results of the study note that: (1) the existence of times and technology that is so fast and 'radical', indirectly affect social and legal changes; (2) the existence of ikhtilÄf among ushuliyÅ«n and related modern figures to make hifzhu al-â€˜irdh as the category of al-dharÅ«riy or al-hÄjiy; (3) with the social transformation that is so fast, then the discourse makes hifzhu al-sebagaiirdh as categorical al-dharÅ«riy is a necessity.